European Commission project: European Guideline for Target Group-Oriented Psychosocial Aftercare-Implementation - Vymetal, Stepan; Deistler, Albert; Bering, Robert; Schedlich, Claudia; Rooze, Magda; Orengo, Francisco; Zurek, Gisela; Krtickova, Michaela (Prehospital and disaster medicine, 2011)
After disasters, the individual health and well-being of first responders and affected population are affected for years. Therefore, psychosocial help is needed. Although most victims recover on their own, a minority of survivors, members of rescue teams, or relatives develop long-term, disaster-related psychic disorders, such as post-traumatic stress disorder (PTSD). This subgroup especially should receive timely and appropriate psychosocial help. Many European countries offer post-disaster psychosocial care from a variety of caregivers (i.e., professionals and volunteers, non-governmental organizations, church or commercial organizations). Therefore, European standards for providing post-disaster psychosocial support currently is required. This article describes the project European Guideline for Target Group-Oriented Psychosocial Aftercare-Implementation, supported by the European Commission.
Keywords: Humans; katastrofy; Guidelines as Topic; přežívající; časná diagnóza; směrnice jako téma; Emergency Responders; stresové poruchy traumatické akutní; medicína katastrof; Survivors; first responder; lidé; Disaster Medicine; Stress Disorders, Post-Traumatic; Social Support; Evropská unie; Disasters; Stress Disorders, Traumatic, Acute; posttraumatická stresová porucha; Mass Screening; Early Diagnosis; plošný screening; sociální opora; European Union